Design and Construction of a Website-Based Bus Ticket Booking Information System - Ichsan, Aulia (InfoTekJar : Jurnal Nasional Informatika dan Teknologi Jaringan, 2024)
In the business world, generally users and owners of companies need something innovative to help support performance and facilitate the use or search for product data. The presence of this website-based internet will make it easier for all groups to access all forms of information, including utilizing the media to be able to connect the relationship between customers and the company's products, namely one of which is ordering bus tickets. Based on the various conveniences and uses of the internet, a "Utilization of Information Systems in Ordering and Digitizing Bus Tickets Based on Websites" was developed. This system is made with PHP, MySQL and Bootstrap software. This Information System is designed to provide convenience in terms of ticket ordering services and obtaining other information needed by customers